2014
DOI: 10.1002/14651858.cd007571.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab for induction and maintenance of remission in ulcerative colitis

Abstract: Moderate to high quality data from four studies shows that vedolizumab is superior to placebo for induction of clinical remission and response and endoscopic remission in patients with moderate to severely active ulcerative colitis and prevention of relapse in patients with quiescent ulcerative colitis. Moderate quality data from one study suggests that vedolizumab is superior to placebo for prevention of relapse in patients with quiescent ulcerative colitis. Adverse events appear to be similar to placebo. Fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 40 publications
0
34
0
4
Order By: Relevance
“…These infections were prob ably related to natalizumab induced blockade of T cell homing to the brain via α4β1 integrins, suggesting that a more specific blockade of α4β7 integrins was important. Subsequently, the α4β7 integrin specific antibody vedolizumab was developed and showed efficacy in clinical phase III trials for remission induction and maintenance in Crohn's disease and ulcerative colitis [58][59][60][61][62][63] .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…These infections were prob ably related to natalizumab induced blockade of T cell homing to the brain via α4β1 integrins, suggesting that a more specific blockade of α4β7 integrins was important. Subsequently, the α4β7 integrin specific antibody vedolizumab was developed and showed efficacy in clinical phase III trials for remission induction and maintenance in Crohn's disease and ulcerative colitis [58][59][60][61][62][63] .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…This systematic review and meta-analysis, which is based on a previously published Cochrane review, 15 summarizes current evidence regarding the use of vedolizumab as an induction and maintenance agent for UC.…”
mentioning
confidence: 99%
“…A recent Cochrane review including four studies with a low risk of bias showed that vedolizumab was superior to placebo for induction of clinical remission and response and endoscopic remission in patients with moderate to severe active UC, and for the prevention of relapse in patients with quiescent UC [43].…”
Section: Anti-integrin Inhibitors Vedolizumabmentioning
confidence: 99%